Optimalisasi Perawatan Sistem Auxiliary Boiler Dalam Menghasilkan Uap Panas - Prasetya Sigit Santosa; Ningrum Astriawati; Salim Salim; Imanuel Agung Prasojo (Politeknik Ilmu Pelayaran Semarang, 2022)
Auxiliary boilers that have the function of producing hot steam are auxiliary steam boilers. The function of this steam is to heat the fresh water jacket cooling and fuel, drive the turbine pump, heat the liquid in the tank and room. This study aims to optimize the maintenance of auxiliary boiler systems, especially in the auxiliary steam boilers. This research was conducted in the engine room on the MT ship. This research is a qualitative descriptive study with data collection obtained from observation, interviews and documentation. The result of this study is the implementation of maintenance of auxiliary boiler components including: Boiler water; main burner; pilot burner; blower; and pumps. Overall, the average before optimizing maintenance, the effectiveness of the implementation of the planning maintenance system in auxiliary boilers was around 58.86%, and the average increased by 27.57% so that the average after optimization of maintenance with the guidelines for planning system maintenance became 86.43%. Auxiliary boiler system maintenance steam boiler In MT Tender Harmony can run optimally so that it can produce quality steam so that it can heat the fuel optimally.